Self-esteem, Achievement Motivation, Self-efficacy and Students’ Anxiety in Speaking - Mettasari, Gustiana (Universitas Pendidikan Ganesha, 2013)
This research aimed at analyzing the contribution of self-esteem, achievement motivation and self-efficacy on students’ anxiety and their anxiety on speaking competency in English. The popu-lation of this study was the first semester students of English Education Department, Ganesha University of Education. This research used correlational design and the data were analyzed by using multiple regression analysis. The results showed that: (1) there was a significant contribution of self-esteem towards students’ anxiety at 33.6%, (2) there was a significant contribution of achievement motivation towards students’ anxiety at 28.7%, (3) there was a significant contribution of self-efficacy towards students’ anxiety at 31.0%, (4) there was a significant simultaneous contri-bution of self-esteem, achievement motivation, and self-efficacy towards students’ anxiety at 40.8%, and (5) there was a significant contribution of students’ anxiety towards students’ speaking competency at 54.0%. Keywords: self-esteem, achievement motivation, self-efficacy, students’ anxiety, speaking competency